System Leadership in Continuing Education in Digital Era Industry 4.0 - Ebe, Lord Steward; Rawis, Joulanda A.M.; Tambingon, Henny N.; Kambey, Joseph (JR Education, 2023)
This research aimed to describe education leadership in continuing education by building the system leadership as a reform system in the professional and modern era. This research is descriptive qualitative research using a social history approach. The design research method was carried out in four phases: data collection, data display, conclusions, and data condensation. The result of this research shows that all education leaders in all levels should be building a system leadership as a reform system for the generation in the modern era to education for sustainable development in Papua.